Diversity, equity, and inclusion in gastroenterology and hepatology: A survey of where we stand. Issue 6 (11th October 2022) - Rahal, Harman K.; Tabibian, James H.; Issaka, Rachel B.; Quezada, Sandra; Gray, Darrell M.; Balzora, Sophie; Yang, Liu; Badiee, Jayraan; May, Folasade P.
Abstract: Background and Aims: In the setting of increasing attention to representation in medicine, we aimed to assess current perspectives of racial and ethnic workforce diversity and health care disparities among gastroenterology (GI) and hepatology professionals in the United States. Approach and Results: We developed and administered a 33‐item electronic cross‐sectional survey to members of five national GI and hepatology societies. Survey items were organized into thematic modules and solicited perspectives on racial and ethnic workforce diversity, health care disparities in GI and hepatology, and potential interventions to enhance workforce diversity and improve health equity. Of the 1219 survey participants, 62.3% were male, 48.7% were non‐Hispanic White, and 19.9% were from backgrounds underrepresented in medicine. The most frequently reported barriers to increasing racial and ethnic diversity in GI and hepatology were insufficient representation of underrepresented racial and ethnic minority groups in the education and training pipeline ( n  = 431 [35.4%]), in professional leadership ( n  = 340 [27.9%]), and among practicing GI and hepatology professionals ( n  = 324 [26.6%]). Suggested interventions were to increase career mentorship opportunities ( n  = 545 [44.7%]), medical student opportunities ( n  = 520 [42.7%]), and program and professional society leadership roles for underrepresented racial and ethnic minority groups ( n  = 473 [38.8%]). Conclusions: Our survey explored imperative and timely perspectives on racial and ethnic representation and health equity among professionals in GI and hepatology. The findings should inform future interventions to address workforce diversity and establish priorities toward improving health equity, ultimately serving as a springboard for professional societies, academic institutions, and other organizations that aim to increase diversity, equity, and inclusion in our field.